Privacy Provision, Payment Latency, and Role of Collateral - Kahn, Charles; Long, Caitlin; Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2020)
The new boundary between publicly and privately provided payments systems and the role of collateral may be changing. Recent technological developments have made it feasible for markets and policymakers to contemplate abolishing physical cash, and replacing it with electronic alternatives like digital tokens. This paper focuses on two concepts: (i) privacy provision that results in increased awareness of and concern with problems of privacy in payments systems; and (ii) payment latency, and how the new fintech world is likely to result in reduced counterparty and interest rate risk for corporate treasurer. The paper ties these issues from the lens of collateral, especially the analogy of collateral reuse and digital tokens.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet